2015
DOI: 10.1039/c4ce01776e
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-assisted synthesis and photocatalytic hydrogen production of mix-phase titanium dioxide (TiO2) nanosheets

Abstract: ARTICLE This journal isNovel mix-phase TiO 2 nanosheets were successfully synthesized by a facile Sol-gel method via using graphene oxide (GO) as the sacrifice template for the first time. The SEM, TEM and AFM images revealed that the thickness of mix-phase TiO 2 nanosheets was ca. 66 nm, and the TiO 2 nanosheets were in a polycrystalline phase and made up of nanoparticles with the diameters of 15-25 nm. In addition, we observed that the proportion of rutile and anatase changed with the amount of tetrabutyltit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Such low crystallinity impurities would act as recombination center. Indeed, the synergy of mixed phase TiO 2 is strongly dependent of the microstructural situation of the present structures [39][40][41]. For this reason, although it has been reported that TiO 2 polymorph junctions (anatase-rutile and even anatase-brookite) [42,43] would show improved photocatalytic performance for hydrogen production with respect to single anatase, in our case, it is expected that the residual presence of other phases could be detrimental.…”
Section: Resultscontrasting
confidence: 47%
“…Such low crystallinity impurities would act as recombination center. Indeed, the synergy of mixed phase TiO 2 is strongly dependent of the microstructural situation of the present structures [39][40][41]. For this reason, although it has been reported that TiO 2 polymorph junctions (anatase-rutile and even anatase-brookite) [42,43] would show improved photocatalytic performance for hydrogen production with respect to single anatase, in our case, it is expected that the residual presence of other phases could be detrimental.…”
Section: Resultscontrasting
confidence: 47%
“…The photocatalytic hydrogen production experiments were carried out in a Lab-H 2 photocatalytic hydrogen production system. 31 A 300 W xenon arc lamp was used as the light source and was positioned 20 cm away from the reactor in the system. In a typical water-splitting over doped STO experiment, 100 mg of the prepared doped STO photocatalyst was dispersed with constant stirring in 200 mL of 20 vol% methanol in aqueous solution.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…Moreover, this system exceeds the photoactivity for hydrogen production when compared to other reports using TiO 2 ,5d, 20 although some catalysts such as TiO 2 /graphene oxide21 and Ag‐doped TiO 2 NPs10 are still more active for this reaction.…”
Section: Resultsmentioning
confidence: 63%